Design patterns for learning games. (15th February 2012) - Kelle, Sebastian; Klemke, Roland; Specht, Marcus
This article concerns the design of self–contained digital games for the life–long learning context. Although the potential of games for teaching and learning is undisputed, two main barriers hamper its wide introduction. First, the design of such games tends to be complex, laborious and costly. Second, the requirements for a sensible game do not necessarily coincide with the requirements for effective learning. To solve this problem, we propose a methodology to the design of learning games by using game design patterns and matching these with corresponding learning functions, which is expected to reduce design effort and help determining the right balance between game elements and learning. First empirical results indicate that such a methodology actually can work.